ANALISIS KEBERLANJUTAN LINGKUNGAN BERDASARKAN KAJIAN LINGKUNGAN HIDUP STRATEGIS DALAM RENCANA TATA RUANG KAWASAN STRATEGIS INDUSTRI SERANG TIMUR (Jurnal Planesa (Planologi), 2016)
Strategic Environmental Assessment (SEA) is a systematic, comprehensive and participatory series of analysis to ensure that the principle of sustainable development has become the basis and integrated in the development of a region and / or policies, plans and / or programs. In the preparation of SEA for Strategic Area of Serang Timur Industry, the substance of RTR of Kawasan Serang Timur Strategic Area is grouped into 3 major components, namely: (1) Industrial Estate Development; (2) Infrastructure; and (3) Land Use and Other Development. Each component is then considered to impact on certain environmental receptors; views of strategic environmental issues that could potentially arise as a result of the implementation of policies, plans and / or programs related to these three components. The result of the scoping is the conflict of utilization of natural resources of Serang Timur area for industrial activities and other non-industrial activities then The high level of land use change to accommodate the development of Strategic Area of Serang Timur Industrial Impact on the decrease of biodiversity and disturbance of ecosystem equilibrium then Provision of infrastructure that emphasizes in the industrial sector rather than environmental services but has not exceeded the environmental carrying capacity of the East Serang region due to the high rate of population growth in the region.Keywords: SEA, scoping, environment and developmen